The Wind In The Willows - Mackinnon,Mairi; Olga,Demidova (London usborne publishing, 2019)
One day, Mole leaves his underground home for the wonderful world of the river. He meets the friendly Water Rat, kind Badger - the Toad, who loves fast cars a little too much
English stories
Keywords: English stories